Flygtige forbindelser og midlertidige mobiliseringer: Om kulturel produktion på Roskilde Festival - Kristine Munkgård Pedersen (Copenhagen Business School (CBS), 2010)
– The dissertation explores how cultural production is unfolding at Roskilde Festival – the biggest music- and culture festival in Denmark. The overall question being adressed is how the festival is assembled. The question is explored through four subquestions related to the cultural expressions, identity and materiality of the festival. The first part of the dissertation investigates the specificity of the festival's audience- based culture. The symbolic and historical connections between the festival and the 1960s' cultural activism is argued to be of an importance to the socioaesthetics, performed jointly by audience as well as performers. The dissertation further investigates how the identity of the festival is being negotiated between a number of different commercial and cultural actors: sponsors, volunteers and artists among others. The many different economic and cultural practices and values converge when the festival ground is being transformed from anonymous space to festival space embracing both cultural and commercial content. In this regard the dissertation investigates how the valuebased economic logics of subcultural production is debated and negotiated during the pratices of materializing space. It is argued that the complexity of the festival identity adds to the credibility of the festival and its many different producers. The second part of the dissertation is a socio-material analysis of two festival projects. One is the hybrid festival area Cosmopol, the other is the Orange Stage area. The analyses are based on a research agenda developed by the Actor- Network-Theory (ANT) which explores how ideas are materialised through proceses of interaction, translation and involvement. The explorations explain how subcultural attitudes, practices of transgression and oppositional identity are distributed through an ephemeral network of actors including humans (volunteers, artists, performers) and things (scenes, art works, graffiti, pictures and music) which forge performative alliances with the festival audience.
hdl:10398/8058
Keywords: 650